Peran Pembelajaran PPKn dalam Membentuk Disiplin Siswa Sekolah Dasar - Khoirunnisa Arbah; Fatonah Salfadilah; Retno Ayu Neng Tiyas; Yuyun Septyana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research is motivated by the low level of discipline among elementary school students, characterized by non-compliance with rules, tardiness, and other negative behaviors, thus requiring the role of Pancasila and Citizenship Education (PPKn) as a strategic solution. This research aims to examine the role of PPKn learning in shaping the discipline of elementary school students through a library research approach. This research method uses a systematic and comprehensive library research method to assess the contribution of PPKn learning in forming the discipline of elementary school students (SD). The main focus is on national scientific sources in Indonesian and English languages from the period 2020-2025, with the aim of identifying patterns and strategies of PPKn learning towards improving student discipline in SD. The study results show that PPKn learning is effective in internalizing discipline values through habituation, teacher exemplification, continuous evaluation, and the use of innovative learning media such as educational videos. The involvement of teachers, schools, and parents is an important factor in supporting the formation of student discipline character, with strategies such as family collaboration and group supervision to overcome external challenges. This research provides a theoretical contribution as a basis for developing applicable PPKn learning strategies to form a disciplined generation in elementary schools. The implications of this study indicate that PPKn learning has a strategic role in shaping the discipline of elementary school students, thus requiring synergy between teachers, schools, and parents to optimize the internalization of character values in every learning activity.